2021
DOI: 10.3390/cancers13050945
|View full text |Cite
|
Sign up to set email alerts
|

Pre-Operative Imaging and Pathological Diagnosis of Localized High-Grade Pancreatic Intra-Epithelial Neoplasia without Invasive Carcinoma

Abstract: Pancreatic ductal adenocarcinoma (PDAC) arises from precursor lesions, such as pancreatic intra-epithelial neoplasia (PanIN) and intraductal papillary mucinous neoplasm (IPMN). The prognosis of high-grade precancerous lesions, including high-grade PanIN and high-grade IPMN, without invasive carcinoma is good, despite the overall poor prognosis of PDAC. High-grade PanIN, as a lesion preceding invasive PDAC, is therefore a primary target for intervention. However, detection of localized high-grade PanIN is diffi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(33 citation statements)
references
References 175 publications
0
33
0
Order By: Relevance
“…This definition, based on MRCP-detected MPD stenosis, facilitated a more accurate evaluation of the time to progression of PCs. However, it should be noted that a definition of first-time detection of MPD stenosis without tumor lesion based on the appearance of MPD stenosis may not be adequate because PCs also arise from the branch pancreatic duct [20]. Furthermore, a genetic and experimental study suggested that transformation of high-grade PanIN into invasive PC required a time period ranging from 3 to 5 years [5].…”
Section: Discussionmentioning
confidence: 99%
“…This definition, based on MRCP-detected MPD stenosis, facilitated a more accurate evaluation of the time to progression of PCs. However, it should be noted that a definition of first-time detection of MPD stenosis without tumor lesion based on the appearance of MPD stenosis may not be adequate because PCs also arise from the branch pancreatic duct [20]. Furthermore, a genetic and experimental study suggested that transformation of high-grade PanIN into invasive PC required a time period ranging from 3 to 5 years [5].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, risk factors included sporadic family history of pancreatic cancer, familial pancreatic cancer, hereditary pancreatic cancer syndrome/hereditary pancreatitis, DM, chronic pancreatitis, heavy alcohol consumption, smoking history, and obesity [ 5 , 21 , 22 , 23 , 24 ]. Imaging findings included the tumor itself and indirect imaging findings (MPD dilation, pancreatic cyst, and IPMN) [ 11 , 14 , 16 , 17 , 25 , 26 , 27 , 28 , 29 ].…”
Section: Methodsmentioning
confidence: 99%
“…These factors have been suggested as suggestive of early stage PDAC detection in many guidelines and reviews [ 5 , 11 , 14 , 21 , 22 , 24 ]. These three new categories and previously reported percentage of each factor in patients with stage 0–Ⅰ PDAC is shown in Figure 1 and Table 1 [ 15 , 26 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations